The Relationship Between Perception of Gender, Autonomy, and Professional Attitude in Nursing Students - Yüksekol, Özlem Doğan; Duman, Mesude; Soylar, Pinar (My University, 2021)
Objectives: This study was conducted to determine the relationship between of nursing students' gender perceptions on their autonomy and professional attitudes. Methods: This is a cross-sectional, descriptive study. This reserach was performed with 215 students studying in the nursing program of a university in eastern Turkey between 25 April and 25 May 2018. The data of the study were collected with Personal Information Form, the Inventory of Professional Attitude at Occupation (IPAO), the Perception of Gender Scale(PGS) and Sociotropy-Autonomy Scale (SAS). Results: It was determined that a positive correlation was found between the PGS score and IPAO (r = 0.229, p
Keywords: Gender; professionalism; Autonomy; Nursing education